Analisis Biaya Perangkat Lunak menggunakan Metode Revised Use Case Point - Inggit Setyo Rini; Widhy Hayuhardhika Nugraha Putra; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Two types of cost estimates are algorithmic and non algorithmic. PT Piramida Teknologi Informasi uses non algorithmic estimate because it estimates based on previous project data and guesstimate. PT Piramida Teknologi Informasi often suffers project delay in processing time in a risk of loss in term of costs. PT Piramida Teknologi Informasi defined the cause of their project problem is the lack of human resource. This study used Revised Use Case Point (RE-UCP) to resolve them. Algorithmic estimate was selected because this type can produce estimate accurately. Re-UCP is algorithmic estimate.Re-UCP was selected because it has more implemented advantages in various project range and close to actual effort value (precision). Re-UCP value was converted into effort in staff hours. Effort becomes the basis of making time and cost allocation. This study did not count the number of human resource but made an allocation for each project activities. SIPAP and SIM JALAN were used as test data in this study. The result showed that SIPAP can be completed at a cost of Rp 184.769.238,37 for 686,7 hours by 7 people. While the SIM JALAN can be completed at a cost of Rp 210.302.26,09 for 568 hours by 8 people. Re-UCP also shows several important things such the development risks that affect cost and time since early phase, possible solutions taken (i.e determined overtime for SIM JALAN), and company's opportunities. The result of this study can be used by project leader or manajer project in making decision such as making scheduling dan knowing benefits of project based on software size.